$\displaystyle \sum_{k=1}^6(-1)^k4^k $ The answer is: 3276 How do you do this problem? $\displaystyle -1^6=1$ $\displaystyle 4^6=4096$ 4096 != 3276 Thanks.
Follow Math Help Forum on Facebook and Google+
Originally Posted by desiderius1 $\displaystyle \sum_{k=1}^6(-1)^k4^k $ The answer is: 3276 How do you do this problem? $\displaystyle -1^6=1$ $\displaystyle 4^6=4096$ 4096 != 3276 Thanks. It is a GP with first term -4, common ratio r = -4 and number of terms 6. So sum S = a[r^n - 1]/(r-1) = -4(4096 - 1)/(-4-1) Now find the answer.
View Tag Cloud